2000
DOI: 10.1038/sj.mp.4000730
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and growth factor involvement in schizophrenia—support for the developmental model

Abstract: Medical treatment with various cytokines can provoke psychiatric symptoms. Conversely, psychiatric patients can display abnormalities in cytokine and neurotrophic factor expression. Such observations have pointed to the potential contribution of cytokines and growth factors to schizophrenic pathology and/or etiology. The cellular targets of the relevant factors and the nature of their actions remain to be explored in mental illness, however. Recent physiological studies demonstrate that cytokines and neurotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(107 citation statements)
references
References 139 publications
4
103
0
Order By: Relevance
“…Experiments using animal models indicate that neurotrophins, particularly BDNF, play a role in neurodevelopmental disorders. 54,58,[105][106][107] Human studies showing altered BDNF levels in schizophrenic patients, both in plasma and the CNS, 54,58 suggest that changes in the expression of BDNF might contribute to the disease pathophysiology, one aspect of which is a disturbed capacity for functional plasticity in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using animal models indicate that neurotrophins, particularly BDNF, play a role in neurodevelopmental disorders. 54,58,[105][106][107] Human studies showing altered BDNF levels in schizophrenic patients, both in plasma and the CNS, 54,58 suggest that changes in the expression of BDNF might contribute to the disease pathophysiology, one aspect of which is a disturbed capacity for functional plasticity in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between infections in mid-gestation and the incidence of schizophrenia in the offspring (reviewed in (Brown, 2006;Patterson, 2008). Cytokine induction due to abnormal immune activation, or inflammation, derails normal brain development leading to alterations in cognition in adulthood (Gilmore and Jarskog, 1997;Nawa et al, 2000;Smith et al, 2007). Recently, using a rodent maternal infection model Smith and collaborators found that maternal IL-6 induction during infection is responsible for the delayed schizophrenia-like behavior observed in the adult offspring (Smith et al, 2007).…”
Section: Neurodevelopmental Origins Of Schizophrenia: Activation Of Tmentioning
confidence: 99%
“…This is similar to the finding of hippocampal pyramidal cell disarray reported in human schizophrenia post-mortem studies [138][139][140] . Because the influenza virus or influenza virus antibodies have not been detected in the fetal brain, it has been hypothesized that the maternal immune response alone is sufficient to generate schizophrenia-like behavioural findings in the offspring 136,[141][142][143][144][145] . At the neurotransmitter level, dysfunctions in the dopaminergic and glutamatergic system have been reported, especially in the medial prefrontal cortex and the nucleus accumbens in offspring from mothers subjected to immune challenge 123 .…”
Section: Maternal Immune Activationmentioning
confidence: 99%